Prevalence of current mental disorders before and during the second wave of COVID-19 pandemic: An analysis of repeated nationwide cross-sectional surveys. (July 2021) - Winkler, Petr; Mohrova, Zuzana; Mlada, Karolina; Kuklova, Marie; Kagstrom, Anna; Mohr, Pavel; Formanek, Tomas
Abstract: Objectives: To assess the prevalence of mental disorders during the second wave of COVID-19 pandemic in comparison with both, baseline and the first wave of the pandemic, and to identify disproportionally affected non-clinical subgroups. Material and methods: We used data from three nationally representative cross-sectional studies and compared the prevalence of current mood and anxiety disorders, and alcohol-use disorders at baseline (November 2017, n = 3306), immediately after the first peak (May 2020, n = 3021), and during the second peak (November 2020, n = 3000) of COVID-19 in Czechia. We used the Mini International Neuropsychiatric Interview (M.I.N.I.) as a screening instrument, and calculated weighted prevalence (%) with 95% weighted confidence intervals (95% CIs). Additionally, we examined the prevalence of these disorders across different non-clinical population sub-groups during the second wave of the pandemic. Results: The proportion of individuals experiencing at least one mental disorder was highest during the second wave of the pandemic (32.94%, 95% CI = 31.14%; 34.77%), when compared to both the baseline in November 2017 (20.02%, 95% CI = 18.64%; 21.39%), and the first wave in May 2020 (29.63%, 95% CI = 27.9%; 31.37%). Younger adults, students, those having lost a job or on forced leave, and those with only elementary education displayed disproportionally high prevalence of mental disorders. Conclusions: Our findings suggest that population mental health has not returned to pre-COVID-19 levels. It seems that mental health of some population subgroups, such as young adults or those worse off economically, might have been affected disproportionately by the COVID-19 situation, and future studies identifying high-risk groups are warranted. Graphical abstract: Image 1 Highlights: We compared the prevalence of current mental disorders in three cross-sectional surveys. Czechs were screened at the baseline and during the 1st and the 2nd wave of COVID-19 pandemic. Mental health sharply declined during the first and did not show any improvement during the second COVID-19 related lockdown. The distribution of mental disorders across non-clinical population sub-groups is uneven. Economically worse-off subgroups display particularly high rates of mental disorders.